The Effect of Job Satisfaction and Employee Commitment on Employee Performance at the Social Service of Makassar City - Karmila Maharani; Romansyah Sahabuddin; Tenri S.P. Dipoatmodjo; Burhanuddin; Zainal Ruma (PT. Maju Malaqbi Makkarana, 2023)
This study aims to (1) determine the effect of job satisfaction on employee performance, (2) determine the effect of employee commitment on employee performance, (3) determine the effect of job satisfaction and employee commitment jointly on employee performance at the Makassar City Social Service . The data used in this study are primary and secondary data with a total sample of 69 respondents. This study used a quantitative approach and was analyzed using multiple linear regression analysis with the help of SPSS 22 data processing to prove three hypotheses. The results of this study prove that the variable Job Satisfaction has a significant effect on Employee Performance with a t count of 2.964 > t table of 1.996. The Employee Commitment variable has a significant effect with a t count of 2.943 > t table of 1.996. Based on the results of this study it is also known that the independent variables jointly or simultaneously have a positive and significant effect on the dependent variable, namely Employee Performance at the Makassar City Social Service. Therefore, if job satisfaction and employee commitment continue to be improved, it will certainly increase employee performance.